Acute abdomen caused by torsion of an undescended testis: A rare presentation and its diagnostic dilemma - Babu M, Narendra; Haldar, Dipanjan; Sahadev, Ravindra; Aihole, Jayalaxmi S (Pediatric Urology Case Reports, 2017)
Most undescended testicles are asymptomatic and diagnosed in the first years of life. In some rare cases the diagnosis is established during childhood due to sudden torsion of the spermatic cord. Additionally, testicular torsion is a well-known urologic emergency that needs to be diagnosed and treated rapidly for the salvage of testis. We are here with reporting a case of torsion of an undescended testis with unusual clinical presentation, as acute abdomen, and its diagnostic dilemma and management.